Peningkatan Ekonomi Komunitas Wanita Tani Melalui Kripik Buah Nanas Di Desa Butuh Kec. Kras Kab. Kediri - izzah , Khoirotul (Proceedings of Annual Conference on Community Engagement, 2022)
the majority village of farmers, the group of women farmers in the village need a village located in the district of Kediri, East Java, to carry out activities to improve the economy, one of which is through pineapple fruit chips, of the many pineapples that are indeed many in the district which are only usually sold fresh fruit which is usually sold as fresh fruit. the selling price is still low, so the village women farmer community needs the district of Kediri, the village women farmer community needs to have an idea to process it into chips so that it has a higher economic value. This community service aims to improve the economy of the women farming community in the Kec Kras Kediri District. The method used in this community service uses participatory action research (PAR), resulting in changes in economic, social, cultural and geographical terms. As a result of community service, it can improve the economy, the productivity of business management from production to marketing for the women's farming community and rural communities needs kec kras Kediri district.